Sediaan Gel Antioksidan Sleeping Mask Kombinasi Ekstrak Etanol Daun Teh Hijau (Camellia Sinensis) dengan Madu Kopi - Titta Hartyana Sutarna; Gladdis Kamilah Pratiwi; Syafa Giana Fathia (Jurnal Impresi Indonesia, 2026)
The combination of green tea leaf extract (Camellia sinensis) and coffee honey can protect teh face from free radical attacks that cause premature aging. This research aims to formulate a gel sleeping mask using green tea leaf extract (Camellia sinensis) and coffee honey. The study began with testing the antioxidant activity of green tea leaf ethanol extract and vitamin C as a comparison to get teh IC50 value using DPPH solution using visible light spectrophotometry. The gel sleeping mask was made with variations in the concentration of coffee honey in 4 formulas, 0% in succession; 1%; 5%; and 10%. Evaluation of gel sleeping mask preparation includes physical evaluation and chemical evaluation. The antioxidant activity test showed that green tea leaf extract had an IC50 value of 16.91 g/ml, while vitamin C had an IC50 value of 5.94 g/ml. Teh results showed that green tea leaf extract and coffee honey could be formulated into a gel sleeping mask as a stable antioxidant during a 28- day storage period. Testing teh antioxidant stability of teh best sleeping mask gel preparation was shown by F3 because it had a percent reduction value of 50.98% after 28 days of storage. The results of the study showed that green tea leaf extract (Camellia sinensis) and coffee honey can be formulated into a sleeping mask gel preparation.